2021
DOI: 10.3389/fimmu.2021.731100
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Helper T Cells in the Immunopathogenesis of SARS-CoV-2 Infection

Abstract: Coronavirus disease 2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a serious infectious disease that has led to a global pandemic with high morbidity and mortality. High-affinity neutralizing antibody is important for controlling infection, which is closely regulated by follicular helper T (Tfh) cells. Tfh cells play a central role in promoting germinal center reactions and driving cognate B cell differentiation for antibody secretion. Available studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 178 publications
2
35
0
Order By: Relevance
“…Accumulated evidence showed the critical role of follicular helper T (Tfh) cells with high expressions of immune checkpoint molecules including TIM-3 and PD-1 in viral infection, including chronic HBV infection ( Ye et al, 2015 ; Vella et al, 2017 ; Zhuo et al, 2017 ; Crotty, 2019 ; Yan et al, 2020 ; Cui et al, 2021 ; Liu et al, 2022 ). In this study, effector CD45RA – CXCR5 + CD4 + Tfh cells with immune checkpoint molecules were detected by flow cytometry ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated evidence showed the critical role of follicular helper T (Tfh) cells with high expressions of immune checkpoint molecules including TIM-3 and PD-1 in viral infection, including chronic HBV infection ( Ye et al, 2015 ; Vella et al, 2017 ; Zhuo et al, 2017 ; Crotty, 2019 ; Yan et al, 2020 ; Cui et al, 2021 ; Liu et al, 2022 ). In this study, effector CD45RA – CXCR5 + CD4 + Tfh cells with immune checkpoint molecules were detected by flow cytometry ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…The TFH cell subsets are essential for inducing high-affinity antibodies [27][28][29][30][31]. The frequency of circulating TFH have been shown to be correlated with neutralizing antibodies in viral infections such as HIV-1 [34], and now SARS-CoV-2 [22,25,35].…”
Section: Discussionmentioning
confidence: 99%
“…Follicular helper T cells (TFH) are primarily defined as CXCR5, programmed cell death protein 1 (PD-1), and Bcl-6 expressing CD4 + T cells. The frequency of circulating TFH cells is often low during homeostasis and is believed to mirror their numbers in the germinal centers of peripheral lymphoid organs, where they provide critical support to antigen-specific B cells to facilitate the development of long-term and high-affinity antibodies [27][28][29][30][31]. Effects on peripheral TFH cells have been documented in a few studies covering acute [32], mild [23],…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found it is signi cantly upregulated in disease conditions by 2.314 Log2FC and has multiple direct connections in the CoVint network. Various investigators have previously reported that downregulation of ICOS transcription factor signi cantly reduces Tfh cells [46][47][48] may lead to B cell differentiation and effective promotion of humoral immune responses 49 and helps in clearing life-threatening viruses including SARS-CoV-2. Therefore, potential inhibitors can be further explored for these proposed targets.…”
Section: Network Analysismentioning
confidence: 99%